COMMUNICATION STRATEGY OF THE REGIONAL LEADERSHIP COUNCIL (DPD) OF THE NASDEM PARTY, SOLOK DISTRICT IN SOCIALIZING ANIES BASWEDAN AS 2024 PRESIDENTIAL CAPTAIN - Rifdah Dzaki, Aflah; Eriend, Dion (Riviera Publishing, 2023)
This research aims to describe the policies or programs of the Solok Regency Nasdem Party in realizing one of its political goals through Anies Baswedan's socialization. In writing this thesis, the author uses a qualitative approach with a qualitative descriptive method, namely, a method for revealing problems by explaining or describing what is in the research by linking the Use and Gratification theory and Hafied Cangara's communication strategy concept. The result of the discussion of this thesis is that the communication strategy implemented by the Solok Regency Nasdem party in the socialization of Anies Baswedan is structured communication from central leadership to administrators to cadres in Solok Regency so that the message can be conveyed evenly. Communication strategy explains the stages in a series of communication activities based on procedures for implementing communication goals. According to Hafied Cangara, there are 5 stages of communication strategy, namely Research, Planning, Implementation, Evaluation and Reporting. The media used are communication media such as billboards distributed in several places, tote bags, calendars and also social media such as the official central Nasdem website, Instagram, WA, Facebook, Twitter, TikTok and so on.